BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA - Irawati Nur; Arfandy Dinsar (Economos : Jurnal Ekonomi dan Bisnis, 2022)
Culture is something that must exist in a human group or organization. The purpose of this study was to determine partially and simultaneously organizational culture and work environment on job satisfaction of employees of the Regional Revenue Agency (BAPENDA) Sidenreng Rappang Regency. Data collection techniques that researchers use in this study are observation, interviews, questionnaires, and documentation. As the population in this study, researchers took employees of the Regional Revenue Agency (BAPENDA) of Sidenreng Rappang Regency who had the status of state civil servants. Thus the number of samples in this study was 43 people. The results of this study indicate that (1) Partial Organizational Culture Variable (X1) has a positive and significant effect on job satisfaction of Regional Revenue Agency employees with a count of 2.021 < from table 2.339 and a significance level greater than 0.05 (sig = 0.024 < 0.05). While the Work Environment variable (X2) has a positive and significant effect on job satisfaction of Regional Revenue Agency employees with t count 2.021 < from t table 3.976 and the significance level is greater than 0.05 (sig = 0.000 <0.05). (2) Simultaneously, the variables of Organizational Culture and work environment from the research results have a positive and significant effect with the calculated F value of 54.297, which is greater than F table 3.24 with a significance value of 0.000 which means below the significance of 0.05.